Development of multi-pixel photon counters for T2K long baseline neutrino experiment - Minamino, A; Nagai, N; Orme, D; Nakaya, T; Yokoyama, M; Nakadaira, T; Murakami, T; Tanaka, M; Retiere, F; Vacheret, A; Kudenko, Y (2008)
We have developed a special 1.3 × 1.3 mm type MPPC (667 pixels with 50 × 50 μm2 each) with Hamamatsu Photonics for the Tokai to Kamioka (T2K) long baseline neutrino experiment. 60,000 MPPCs will be used in the T2K neutrino detectors, which will be the first time that MPPCs have been used on such a large scale. We tested 17,000 MPPCs for the T2K near detectors. We report on the basic performance of the MPPCs. ©2008 IEEE.